2018
DOI: 10.1016/j.antiviral.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing potential of 1st generation H1-specific antihistamines as anti-filovirus therapeutics

Abstract: Ebola and Marburg are filoviruses and biosafety level 4 pathogens responsible for causing severe hemorrhagic fevers in humans with mortality rates up to 90%. The most recent outbreak in West Africa resulted in approximately 11,310 deaths in 28,616 reported cases. Currently there are no FDA-approved vaccines or therapeutics to treat infections of these deadly viruses. Recently we screened an FDA-approved drug library and identified numerous G protein-coupled receptor (GPCR) antagonists including antihistamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Clemastine is used to relieve hay fever and allergy symptoms. Antihistamine drugs have been reported in the past to have certain antiviral effects [ 21 – 23 ]. In a previous report that used the SARS-CoV-2 viral protein interactome to identify antiviral drugs, Gordon et al reported that clemastine is an active antiviral agent targeting the Sigma 1 and Sigma 2 receptors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clemastine is used to relieve hay fever and allergy symptoms. Antihistamine drugs have been reported in the past to have certain antiviral effects [ 21 – 23 ]. In a previous report that used the SARS-CoV-2 viral protein interactome to identify antiviral drugs, Gordon et al reported that clemastine is an active antiviral agent targeting the Sigma 1 and Sigma 2 receptors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, several antihistamines, such as chlorcyclizine, chlorpheniramine, and diphenhydramine, have demonstrated antiviral action against hepatitis C virus (HCV), filoviruses (consisting of Ebola virus, Marburg virus, and Cuevavirus), and Influenza A virus infection [78][79][80]. Of note, ketotifen fumarate has proven to attenuate dengue virus infection [81].…”
Section: Antiallergic Eye Dropsmentioning
confidence: 99%
“…Most of these inhibitors target events occurring in the endosome, such as GP proteolytic processing, endosomal trafficking, interactions with NPC1, and fusion, including: (1) CA-074, FY-DMK, CID23631927, K11777, and cathepsin B and L inhibitors [29,30,37,38,39,40,41]; (2) inhibitors targeting host factors in the late endosomal steps in EBOV entry, such as U18666A, MBX2254, and MBX2270, targeting NPC1 [19,20,42], and numerous L-type calcium channel inhibitors, including verapamil, tetrandrine, nimodipinee, and diltiazem [10]; (3), a group of selective estrogen receptor modulators (SERMs), such as clomiphene and toremifene, which can directly bind to Ebola GP [36,43]; and (4) numerous G-protein coupled receptor (GPCR) antagonists such as antihistamines, targeting Ebola virus (and Marburg virus) GPs [34,44]. Only the first generation of antihistamines, such as diphenhydramine and chlorcyclizine, effectively block entry of Ebola virus and Marburg viruses, consistent with the notion that these compounds exert their antiviral effect in the endosomes [26].…”
Section: Discussionmentioning
confidence: 73%
“…We used a similar docking method as reported in our previous publication [26]. Briefly, the GLIDE module (SchrĂśdinger 10.0, Portland, OR, USA) within SchrĂśdinger Suite 2014 was used to rank the best conformations and orientations of the ligand based on its interactions with the Ebola virus GP (PDB code, 5JQ7) The LigPrep (including Ionizer) module and Macromodel module was used to generate three-dimensional coordinates of the ligands and protein with calculated ionization states.…”
Section: Methodsmentioning
confidence: 99%